2015
DOI: 10.1016/j.conbuildmat.2015.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring chloride-induced corrosion of carbon steel tendons in concrete using a multi-electrode system

Abstract: h i g h l i g h t sA novel multi-reference-electrode (MuRE) was proposed and studied. Nickel and stainless steel were the more stable metals for the reference electrode. The MuRE is able to detect and locate the chloride-induced corrosion. The proper length of each wire is influenced by the cover and the resistivity. The maximum allowable length/cover ratio to detect the localized corrosion is 50. To monitor real-time the occurrence of localized corrosion in reinforced concrete structures a novel multi-referen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In embedded systems, the reference electrode is inserted in the concrete and is on the concrete surface in the case of portable systems, see Figure 3. In the first system, the connection to the reinforcement is made before concrete insertion, it being necessary that the steel is exposed to make the connection in the portable systems [21].…”
Section: Measurement Of Electrochemical Potentialmentioning
confidence: 99%
“…In embedded systems, the reference electrode is inserted in the concrete and is on the concrete surface in the case of portable systems, see Figure 3. In the first system, the connection to the reinforcement is made before concrete insertion, it being necessary that the steel is exposed to make the connection in the portable systems [21].…”
Section: Measurement Of Electrochemical Potentialmentioning
confidence: 99%
“…Although a lot of investigations have been conducted on the field measurements and mitigation of metro stray current interference suffered by buried pipeline, only a few research work studied the corrosion behavior and corrosion rate assessment method under dynamic DC stray current. [12][13][14][15][16] McCollum and Ahlborn [12] conducted a study in which iron samples were subjected to alternating and infrequently reversed current for different periods of time. The resulting corrosion was compared to corrosion produced by a steady-state DC of the same current density and discharge period.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that both the stray current density and the soil conductivity were the main factors affecting the corrosion rate, whereas the stray current frequency from 5 to 30 Hz contributed less to the corrosion rate. Brenna et al [14] carried out weight loss tests in the soil-simulating environment on cathodically protected carbon steel specimens by changing DC interference amplitude (0.1, 1, and 10 A/m 2 ) and the peak duration and they proposed that due to the alkalinity from oxygen reduction and hydrogen evolution reactions, the steel was under passive condition during the cathodic period, whereas within the anodic period, initially, the anodic reaction occurring on the metal caused the progressive neutralization of the electrolyte in contact with steel, resulting in the loss of passive condition of the steel, and then anodic corrosion occurred. Huo et al [15,16] adopted new electrochemical testing cells to conduct DC interference experiments and investigated the effects of potential excursions and pH variations on corrosion behavior.…”
Section: Introductionmentioning
confidence: 99%
“…The specific feature of corrosion in concrete is that the anodic and cathodic sites are spatially localized due to the porous structure of the concrete [5], while the porosity of the concrete also affects the transport of the electrolyte and oxygen, determining the dynamics of the corrosion processes [27]. Therefore, certain new or upgraded methods were developed, enabling the continuous monitoring of corrosion [28][29][30][31]. One specific type of embedded sensor is the electrical resistance (ER) probe, which measures the thickness reduction due to corrosion [28].…”
Section: Introductionmentioning
confidence: 99%